Variability of Data in High Throughput Experimentation for Catalyst Studies in Fuel Processing - Niels T.J. Luchters; J. V. Fletcher; S. J. Roberts; J. C. Q. Fletcher (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
The use of high throughout and combinatorial experimentation is becoming commonplace in catalytic research. The benefits of parallel experiments are not only limited to reducing the time-to-market, but also give an opportunity to study processes in more depth, by generating more data. To investigate the complete parameter space, multiple experiments must be performed and the variability between these experiments must be quantifiable. In this project, the reproducibility and variance in high throughput catalyst preparation and parallel testing were determined. High-performance equipment was used in a catalyst development program for fuel processing, the production of fuel cell-grade hydrogen from hydrocarbon fuels. Four studies, involving water-gas shift conversion and high-temperature steam methane reforming, were performed to determine the reproducibility of the workflow from automated catalyst preparation to parallel activity testing. Statistical analyses showed the standard deviation in catalytic activities as determined by conversion, to be less than 6% of the average value.